Influence of titanium surface treatments on viability of periodontal fibroblasts grown in an osteogenic culture medium - Daniela de Morais Rocha; Marcelo Luchesi Teixeira; Luis Guilherme Scavone de Macedo; André Antonio Pelegrine; Antonio Carlos Aloise (Wolters Kluwer Medknow Publications, 2022)
Background: The integrity of the protective seal provided by the gingiva in direct contact with the implant surface is one of the main factors involved in the prevention of peri-implantitis. Aim: The aim of this study was to assess the viability of periodontal fibroblasts grown in an osteogenic culture medium in contact with titanium surfaces treated either with acid etching alone or with acid etching + anodizing. Materials and Methods: Periodontal fibroblasts grown in an osteogenic culture medium were distributed in a control group, with cells grown in culture bottles, and two experimental groups, with cells grown in contact with titanium disks measuring 6 mm in diameter. The surface of the disks was subjected to acid etching alone (AEG, n = 25) or to acid etching + anodizing (ANG, n = 25), and then evaluated using scanning electron microscopy (SEM). Cell viability was assessed by the [3-(4,5-dimethylthiazol-2yl)-2,5-diphenyl tetrazolium] bromide test on days 1, 2, 3, 7, and 14 of the cell culture. The Mann-Whitney test was used for the statistical analysis (P < 0.05). Results: The SEM assessment revealed that the surface of AEG specimens had micrometric characteristics, whereas the surface of ANG specimens had nanometric characteristics. No significant difference was observed among the groups regarding cell viability at any of the evaluation time points. Conclusion: The titanium surface treatments tested did not affect the viability of periodontal fibroblasts in an osteogenic culture medium.